Media Sosial dan Tantangan Masa Depan Generasi Milenial - Amar Ahmad; Nurhidaya Nurhidaya (Avant Garde, 2020)
Millennial generation is a generation born between the 1980s and the present. This generation is very familiar with the world of digital -based technology . The use of gadgets is part of their lifestyle. Instant technology users have facilitated the various activities of this millennial generation. The use of media , especially social media among the millennial generation, is often the attention and spotlight of various groups ranging from the executive, legislative, judiciary, as well as a number of elements of society such as teachers, lecturers, education observers and of course parents do not miss. The number of social media users among the millennials is big enough namely 93%, therefore it is necessary to look at how to use it so that it can lead to a more positive direction, including optimizing the resources of the millennial generation in an effort to improved the nation’s economy by optimizing various online-based creative industries . This paper was conducted using a Library Research approach using Henry Jenkins' social media theory, namely the Participatory Media Culture theory. In his theory, Jenkins describes a number of approaches and mechanisms by individuals or certain audiences which collectively take on the role of media consumers as well as act as producers of certain information from the existing media. This study is expected to contribute to all existing stakeholders.